Isolation of a Spotted Fever Group Rickettsia, Rickettsia peacockii, in a Rocky Mountain Wood Tick, Dermacentor andersoni, Cell Line - Simser, Jason A. (American Society for Microbiology, 2001)
An embryonic cell line (DAE100) of the Rocky Mountain wood tick, Dermacentor andersoni, was observed by microscopy to be chronically infected with a rickettsialike organism. The organism was identified as a spotted fever group (SFG) rickettsia by PCR amplification and sequencing of portions of the 16S rRNA, citrate synthase, Rickettsia genus-specific 17-kDa antigen, and SFG-specific 190-kDa outer membrane protein A (rOmpA) genes. Sequence analysis of a partial rompA gene PCR fragment and indirect fluorescent antibody data for rOmpA and rOmpB indicated that this rickettsia was a strain (DaE100R) of Rickettsia peacockii, an SFG species presumed to be avirulent for both ticks and mammals. R. peacockii was successfully maintained in a continuous culture of DAE100 cells without apparent adverse effects on the host cells. Establishing cell lines from embryonic tissues of ticks offers an alternative technique for isolation of rickettsiae that are transovarially transmitted.